37th Structure, Structural Dynamics and Materials Conference 1996
DOI: 10.2514/6.1996-1381
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alternative wing structural concepts on high speed civil transport life cycle costs

Abstract: An integrated design and manufacturing approach allows economic decisions to be made that reflect the entire system design as a whole. In order to achieve this objective, integrated cost and engineering models were developed and utilized within a focused design perspective. A framework for the integrated product and process design of an aircraft system with a combined performance and economic perspective is described in this paper. This framework is based on the concept of Design Justification using a Design f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Structural efficiency is already a tradeoff between maximizing material strength utilization and reducing weight, 45 whereas manufacturing cost is a tradeoff between specified design requirements (within tolerance) and process capability. 46 Equation (29) highlights that the tradeoff can be achieved through the minimization of DOC: DOC = f n(acquisition, fuel burn, maintenance, crew and navigation, ground services)…”
Section: Methods Of Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural efficiency is already a tradeoff between maximizing material strength utilization and reducing weight, 45 whereas manufacturing cost is a tradeoff between specified design requirements (within tolerance) and process capability. 46 Equation (29) highlights that the tradeoff can be achieved through the minimization of DOC: DOC = f n(acquisition, fuel burn, maintenance, crew and navigation, ground services)…”
Section: Methods Of Optimizationmentioning
confidence: 99%
“…28 Marx et al have linked MDO to life-cycle analysis (LCA) by defining high-level objective functions that encompass the lifecycle needs of aircraft, supported by necessary disciplinary models that facilitate the optimization process through the linkage defined by an objective function. 29 In aerospace, LCA tends to be associated with military application, whereas the commercial sector focuses on DOC, being more associated with the cost of transporting a person a number of air miles at as low a cost as possible. There are various DOC models available, which tend to be of a parametric nature, 30,31 that allow tradeoff of design parameters and that can be linked to manufacturing models to couple in the impact on production.…”
Section: Literature Review: Cost Integrated Designmentioning
confidence: 99%
See 1 more Smart Citation
“…assessing the trade-off between technologies or materials using a life cycle approach). Marx et al [14] linked MDO to life cycle analysis by defining high level objective functions that encompass the life cycle needs of the aircraft. Hackney and Neufville [15] described a life cycle model for performing comparisons of emissions, costs, and energy efficiency trade-offs for alternative fuel vehicles.…”
Section: Cost Engineeringmentioning
confidence: 99%
“…IPPD is seen as a management methodology that incorporates a systematic approach to the early integration and concurrent application of all the disciplines that play a part throughout a system's life cycle [11,12]. Best commercial practices in industry have revealed that world class quality and affordable products are achieved through IPPD.…”
Section: Life-cycle Multi-disciplinary Designmentioning
confidence: 99%